Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3329/jujbs.v7i2.40746
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of Angiosperms extant in Mirpur area of Dhaka city

Abstract: This study has recognized the occurance of a total of 346 species of Angiosperms under 256 genera and 82 families and assessed their current status and distribution in Mirpur area of Dhaka district. Majority of these families, 68 (82.92%) consist of 255 species under 192 genera, belong to Magnoliopsida (dicotyledons), and the rest 14 (17.07%) comprise of 91 species under 64 genera to Liliopsida (monocotyledons). Asteraceae with 18 species is found to be the largest family in Magnoliopsida followed by Euphorbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The species diversity recorded from the studied brickfield areas of Savar and Dhamrai region is consistent with the reports on few forest areas (Rahman & Hassan, 1995;Rashid & Mia, 2001) and semi-urban to rural areas (Alam et al, 2006;Rahman et al, 2012;Shetu et al, 2018;Nahaer, 2014). To know the exact reasons of the occurrence of higher species composition and diversity of vascular plants in and around the brickfield areas of Savar and Dhamrai region than those of some plain land areas of Bangladesh, as reported by some previous studies, further comparative studies involving more parameters are necessary.…”
Section: Species Diversitysupporting
confidence: 88%
“…The species diversity recorded from the studied brickfield areas of Savar and Dhamrai region is consistent with the reports on few forest areas (Rahman & Hassan, 1995;Rashid & Mia, 2001) and semi-urban to rural areas (Alam et al, 2006;Rahman et al, 2012;Shetu et al, 2018;Nahaer, 2014). To know the exact reasons of the occurrence of higher species composition and diversity of vascular plants in and around the brickfield areas of Savar and Dhamrai region than those of some plain land areas of Bangladesh, as reported by some previous studies, further comparative studies involving more parameters are necessary.…”
Section: Species Diversitysupporting
confidence: 88%
“…Studies on the flora of urban or semi-urban areas has long been neglected by the taxonomists, because the ecosystems of these areas have been regarded as highly disturbed and supporting relatively common species only. However, some taxonomic surveys have been completed on or covering some (semi-) urban areas (Alam et al, 2006;Sultana, 2012;Rahman et al, 2013;Tabassum, 2015;Shetu et al, 2018;Khanam et al, 2020;Roy and Khan, 2020). Studies on the flora of few campus areas have also been conducted (Momen et al, 2006;Uddin and Hassan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…al. (2016), Shetu et al (2018) and Uddin and Hassan (2012) in respect to the size of sampling area. The number of pteridophyte species found in the homesteads of the study area seems similar to that reported by Sarker and Hossain (2009) from greater Mymensingh district.…”
Section: Resultsmentioning
confidence: 99%